Festival food coma in cystic fibrosis1. Issue 7 (9th November 2012) - Pandit, Chetan; Graham, Christie; Selvadurai, Hiran; Gaskin, Kevin; Cooper, Peter; van Asperen, Peter
Abstract Children with cystic fibrosis liver disease and portal hypertension are at risk of developing acute hepatic encephalopathy. Even in the presence of normal synthetic liver function these children may have porto‐systemic shunting. We report a case of an adolosecent who had cystic fibrosis liver disease and presented with life threatening hepatinc encephalopathy. This case illustrates that it is necessary to consider an appropriate dietary regimen in adolosecents with liver disease to prevent hepatic decompensation. Pediatr Pulmonol. 2013; 48:725–727. © 2012 Wiley Periodicals, Inc.